On Factors behind the Reasonable Failure Mode of Concrete-Filled Circular Steel Tubular Composite Frame - Yang-bing Liu; Ping-ping Cui; Fang Chen (Advances in Materials Science and Engineering)
As the most basic structure, the concrete-filled steel tubular (CFST) frame has been widely used in various structures and systems. Compared with conventional reinforced concrete structures and steel structures, CFST structures in strong earthquake showcase more complicated strength and deformation behavior because there are many factors underlying the failure mode. Furthermore, according to the specifications at home and abroad, the corresponding design method to achieve reasonable failure modes for CFST structures has not been clarified. Based on a destructive test on steel beam-CFST plane frames under constant axial load and lateral load, the fiber mode method and solid element model method are adopted to simulate the failure process of the test frames. Based on finite element model simulations and tests, the fiber model method is proposed to carry out the pushover analysis on the CFST frame structures. The factors behind the reasonable failure mode of steel beam-concrete-filled circular steel tubular (CFCST) frame structures are analyzed. Furthermore, the law and influencing factors behind the ratio of flexural capacity of column to beam, the ratio of line stiffness of beam to column, and the ratio of axial compression on the deformation, bearing capacity, and failure modes of the structure are discussed. Some suggestions on the design of reasonable failure mode of steel beam-concrete-filled circular steel tubular (CFCST) frame structures are proposed.